Analisis Kepuasan Konsumen Berdasarkan Pelayan Dan Kualitas Makanan Menggunakan Metode Fuzzy Mamdani (Studi Kasus : Cafe Talasi) - Trisno; Titus Kurra; Yulius Ama (Universitas Medan Area, 2023)
The development of the culinary business in Indonesia in general grows and spreads in various regions and continents in view of the development of the industry in Indonesia, which is increasing day by day. The culinary business is one of the most widely run businesses to date. System design to obtain output is carried out in several stages, namely: forming fuzzy sets, application of implication functions (formation of fuzzy rules), composition of fuzzy rules, assertion (defuzzification). From the results of research that has been done obtained. The input consists of the level of service obtained by real numbers. given is the taste of food with a value of 4 with the domain [4 5]. That is, the variable taste of good food. From the service quality input, a value of 3 is obtained with the domain [3 4]. That is, the service quality variable is quite good. From the input given, the output level of consumer satisfaction is 4.93%, which means that customers are satisfied with the taste of the food and the quality of service provided by the Talasi café.